Analysis of Broken Connector Defects on the G0FL Line Using the PDCA Method in a Wiring Harness Company - Gilang Fachrat Firmansyah; Hery Irwan (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
Product quality is a critical determinant of competitiveness in the wiring harness industry because defects in connector components may disrupt electrical continuity, assembly performance, and customer satisfaction. One recurring problem found on the G0FL line of a wiring harness company was broken connector defects, which contributed significantly to total line defects. This study aims to analyze the causes of broken connector defects and propose quality improvement actions using the Plan-Do-Check-Act method supported by seven quality control tools. The research was conducted through direct observation, defect data collection, Pareto analysis, cause-and-effect analysis, 5W+1H analysis, and before-after defect comparison. The initial observation showed that broken connector defects accounted for the largest proportion of defects on the G0FL line. Root cause analysis indicated several dominant causes, including improper handling, unstable material positioning, insufficient operator awareness, inappropriate work methods, and weak process monitoring. Improvement actions were implemented through work instruction revision, operator retraining, jig and handling standardization, visual control, and routine defect monitoring. After implementation, the broken connector defect rate decreased from 0.81% to 0.30%, representing a reduction of 62.96%. The findings show that the PDCA method is effective as a structured continuous improvement approach for minimizing connector-related defects in wiring harness production.